Secular Pegs and God-Shaped Holes: The Uneasy Alliance of the Religious, the Spiritual and the Secular in Recent Art for the Church - Koestlé-Cate, Jonathan (Journal for the Study of Spirituality, 2012)
It is sometimes claimed that contemporary Western culture has at its heart a God-shaped hole. It is an accusation more specifically levelled at modern art whenever it makes incursions into the church, especially when so many of the chosen artists openly admit to being atheists or agnostics. For some, the increasing use of non-confessional artists to produce work for the church is seen as a symptom of this spiritual vacuum; conversely, for others it signifies a repudiation of the premises of this thesis, in that spiritual values are judged to be no less evident just because a conventionally religious sensibility appears to be absent. An unlikely response to this debate may be discerned in Badiou’s philosophy of the situated void; unintentionally offering an incisive perspective on this question of a God-shaped hole, his ideas disclose the possibility of a rapprochement between theology, spirituality and art.